HAD fabricated on UTB AlGaN/GaN heterostructure for high‐sensitivity zero‐bias microwave detection. Issue 24 (1st November 2019) - Yun, Yu; Xiong, Wei; Shi, Yu; Chen, Kuangli; Zhou, Qi
Abstract : A novel technology based on aluminium gallium nitride (AlGaN)/GaN hybrid‐anode diode (HAD) for precise modulation of turn‐on voltage is proposed and experimentally demonstrated. By delicately tailoring the as‐grown barrier thickness, the turn‐on voltage of the HAD and yet the non‐linearity at zero bias (i.e. 0 V) for efficient microwave detection can be flexibly modulated. An AlGaN/GaN ultra‐thin‐barrier HAD (UTB‐HAD) was designed and fabricated for zero‐bias microwave detection. The AlGaN‐barrier thickness was optimised to be 5 nm by TCAD simulation, which yields a strong non‐linearity at zero bias featuring a high‐curvature coefficient ( γ ) of 27 V −1 in the fabricated UTB‐HAD. The first‐order voltage sensitivity β V is projected to be as high as 2.7 mV/μW. The proposed approach of precise sensitivity modulation is of great interests for high‐efficient zero‐bias microwave detection applications.